Performance of a campus photovoltaic electric vehicle charging station in a temperate climate. (1st January 2019) - Esfandyari, Ayda; Norton, Brian; Conlon, Michael; McCormack, Sarah J.
Highlights: A campus PV EV charging station for operation under temperate climates was designed. Design options for deployment of an AC coupled battery PV EV charging considered Performance indicators were calculated via simulation algorithms in MATLAB. Simulation outputs were compared to monitored data. CO2 emissions avoided as well as carbon tax savings were calculated. Abstract: A photovoltaic (PV) array can be combined with battery energy storage to satisfy the electrical demand of lightweight electric vehicles. Measured solar resource and vehicle energy consumption, together with locational, mechanical and electrical constraints were used to design a vehicle charging station comprised of a 63 m 2 10.5 kW AC PV array, with a 9.6 kWh lithium-ion battery. PV output, battery charge and discharge, electricity flows were monitored over one year. Deviations between measured and calculated annual AC generation averaged to 14%. Average annual direct consumption, self-consumption and system self-sufficiency were 8.47%, 30.3% and 74.36% respectively.